Development of methodological approaches to identify the risks of malfunctions and failures and determine their criticality for mining dump Trucks - Chernyh V.G.; Otrokov A.V.; Grinko D.A.; Grinko A.A.; Mironova A.O.; Bogatyrev A.R. (Горное оборудование и электромеханика)
Mining companies strive for maximum efficiency and safety. Quarry dump trucks (CS), being a key link, play a critical role in ensuring the smooth operation of the enterprise. The use of a risk-based approach to MRO makes it possible to minimize negative consequences by timely identifying and eliminating potential problems, which makes it relevant to develop methodological approaches to identifying and assessing the criticality of CS failure risks. This work is devoted to the development of methodological approaches to the identification, classification and assessment of the criticality of CS failure risks in order to optimize the MRO strategy and increase operational efficiency. The article discusses various aspects related to the reliability and safety of CS operation, and suggests practical solutions to improve their operational readiness. As part of the study, an analysis of existing methods for assessing the risks of technical system failures was carried out. Taking into account the specifics of CS operation in the conditions of mining enterprises, the most appropriate approach was chosen. An analysis of existing standards describing recommendations for ensuring equipment reliability and risk management has been carried out. Based on the standards, methodological approaches to the identification of failure risks have been developed and a multi-criteria system for classifying risks by criticality levels has been proposed, taking into account the likelihood of failure, potential consequences for the production process, personnel safety and the environment. Based on the developed risk classification, recommendations have been formulated for optimizing the MRO plan of the CS, including determining the optimal frequency of preventive maintenance. The developed approach allows us to rank the risks of CS failures by criticality and form informed decisions on the priority of MRO, resource allocation and cost optimization. The application of the methodology helps to increase the efficiency of MRO, reduce downtime, minimize financial losses and improve the safety of CS operation.